DIELECTRIC BEHAVIOR OF SLUDGE FROM WASTEWATER TREATMENT - BARTHA, Csaba; CARAMITU, Alina; JIPA, Monica; IGNAT, Daniela Maria; TÓKOS, Attila (Studia Universitatis Babeș-Bolyai Chemia, 2020)
In the present study, dielectric spectroscopy was used to assess the influence of ELF (1-200 Hz) electromagnetic fields over protein relaxation from activated sludge (approx. 99% water content), sampled from the biological tank of a domestic wastewater treatment plant. Dielectric loss (tgδ) was determined for both activated sludge samples and autoclaved samples. Experimental data analysis shows that biological samples (activated sludge) have different dielectric behavior than the sterile samples (sterilized sludge). Unlike sterile samples in which the function tgδ vs. frequency is continuous, in the activated sludge samples, this function presents two discontinuities specific to electrical resonances around the frequencies of 26.5 Hz and 50.1 Hz. This behavior indicates that under the influence of the measuring signal of 26.5 Hz and 50.1 Hz, biochemical processes are stimulated in activated sludge. Also, the significant changes in the number of charge carriers suggest that, at these frequencies, changes occur in the mechanism and kinetics of biochemical processes.